PENGARUH MODAL KERJA TERHADAP RENTABILITAS EKONOMI PADA KOPERASI SAWIT USAHA MAJU DI KECAMATAN KAMPAR KIRI TENGAH - Sitanggang, Paskaria Martiana; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Cooperatives are business entities consisting of people who organize the utilization of economic resources of their members based on family principles that aim to improve the level of members in particular and the regional community in general, thus cooperatives are the people's economic movement and the national economy teacher . Cooperatives have social character, so to obtain the remaining results of business is not the main goal. Another goal to achieved from each cooperative is how cooperatives are able to create and maintain business relationships with customers to obtain the expected profit. The ability to produce effective profits is usually referred to as Rentability.This research is a quantitative descriptive study with the aim to determine the effect of working capital (Cash Turnover, Receivable Turnover, and Inventory Turnover) on economic rentability both partially and simultaneously in the Advanced Business Palm Cooperative in the Central Left Kampar District. The results of the research conducted partially are influential Cash Turnover and accounts receivable turnover have effect on economic rentability, while inventory turnover have no effect on economic rentability. Meanwhile simultaneous cash turnover, accounts receivable turnover and inventory turnover have effect on economic rentability.Â Keywords: Cash Turnover, Accounts Turnover, Inventory Turnover, economic RentabilityÂ